Effect of a typical systemic hospital reform on inpatient expenditure for rural population: the Sanming model in China - Zhaolin Meng; Min Zhu; Yuanyi Cai; Xiaohong Cao; Huazhang Wu (BMC, 2019)
Abstract Background Considering catastrophic health expenses in rural households with hospitalised members were unproportionally high, in 2013, China developed a model of systemic reform in Sanming by adjusting payment method, pharmaceutical system, and medical services price. The reform was expected to control the excessive growth of hospital expenditures by reducing inefficiency and waste in health system or shortening the length of stay. This study analyzed the systemic reform's impact on the financial burden and length of stay for the rural population in Sanming. Methods A total of 1,113,615 inpatient records for the rural population were extracted from the rural new cooperative medical scheme (NCMS) database in Sanming from 2007 to 2012 (before the reform) and from 2013 to 2016 (after the reform). We calculated the average growth rate of total inpatient expenditures and costs of different medical service categories (medications, diagnostic testing, physician services and therapeutic services) in these two periods. Generalized linear models (GLM) were employed to examine the effect of reform on out-of-pocket (OOP) expenditures and length of stay, controlling for some covariates. Furthermore, we controlled the fixed effects of the year and hospitals, and included cluster standard errors by hospital to assess the robustness of the findings in the GLM analysis. Results The typical systemic reform decreased the average growth rate of total inpatient expenditures by 1.34%, compared with the period before the reform. The OOP expenditures as a share of total expenditures showed a downward trend after the reform (42.34% in 2013). Holding all else constant, individuals after the reform spent ¥308.42 less on OOP expenditures (p < 0.001) than they did before the reform. Moreover, length of stay had a decrease of 0.67 days after the reform (p < 0.001). Conclusions These results suggested that the typical systemic hospital reform of the Sanming model had some positive effects on cost control and reducing financial burden for the rural population. Considering the OOP expenditures as a share of total expenditures was still high, China still has a long way to go to improve the benefits rural people have enjoyed from the NCMS.